Changes in Kernel Filling with Selection for Grain Yield in a Maize Population. Issue 2 (1st March 2015) - Eichenberger, Steve; Miguez, Fernando; Edwards, Jode; Knapp, Allen
ABSTRACT: Genetic improvement in kernel filling characteristics has been an important contributor to hybrid maize ( Zea mays L.) yield increases. However, changes in kernel filling characteristics have not been evaluated within the context of recurrent selection programs. The objective of this study was to determine if rate and duration of kernel filling and their interaction with plant density changed with long‐term recurrent selection for agronomic performance in the Iowa Stiff Stalk Synthetic (BSSS) population. Populations selected for improved grain yield and agronomic performance were compared with the unselected base population, BSSS, at average final plant densities of 4.7 and 6.6 seeds m −2 at two locations near Ames, IA in 2009 and 2010. Treatments were replicated three times per location in a split plot design. Selected populations had a longer period of kernel filling but did not have a higher rate of kernel filling. Selected populations also had reduced final kernel weight at higher plant density, whereas unselected populations did not differ in final kernel weight. Reduction in final kernel weight at high plant density in selected populations suggests that increases in grain yield at high plant density in selected populations resulted from components of grain yield other than final kernel weight.